A comparison of the efficacy, safety, and duration of frame-based and Remebot robot-assisted frameless stereotactic biopsy. (4th May 2021) - Wu, Shiqiang; Wang, Junwen; Gao, Pan; Liu, Weihua; Hu, Feng; Jiang, Wei; Lei, Ting; Shu, Kai
Abstract: Objective: The aim of this study was to compare the efficacy, safety, and duration of Remebot robot-assisted frameless brain biopsy with those of standard frame-based stereotactic biopsy. Patients and methods: A retrospective analysis of 66 patients undergoing stereotactic brain biopsy in our department from January 2015 to January 2019 was performed. We divided the patients into two groups: the frame-based group ( n  = 35) and the Remebot robot group ( n  = 31). Data on clinical characteristics, total procedure length, overall discomfort, diagnostic yield, complications, and postoperative length of hospital stay were retrospectively reviewed and compared between these two groups. Results: No significant difference in diagnostic yield was detected in the two groups, with frame-based biopsy having a diagnostic yield of 91.4% and Remebot robot-assisted frameless brain biopsy having a diagnostic yield of 93.5%. The duration of the total procedure was 116.5 min for the frame-based biopsy and 80.1 min for the Remebot robot-assisted frameless brain biopsy ( p  < 0.001). There were no statistically significant differences in complication rate or postoperative duration of hospitalization between the two groups. The overall patient discomfort in the frame-based group was significantly greater than that in the Remebot robot group (visual analog scale score 2.7 ± 1.2 versus 1.5 ± 0.7, p  = 0.001). Conclusions: Remebot robot-assisted frameless brain biopsy was as efficacious and safe as standard stereotactic frame-based biopsy. However, frameless biopsy can alleviate the suffering of the patient and reduce the total duration of the procedure. Remebot robot-assisted frameless brain biopsy is easy to use and better accepted by patients than frame-based biopsy.